Education, Human Rights and Peace in Sustainable Development - Nugmanova, Maigul; Mikkola, Heimo; Rozanov, Alexander; Komleva, Valentina (IntechOpen, 2020)
The aim of sustainable development is to balance our economic, environmental and social needs, allowing prosperity for current and future generations. Countries must be allowed to meet their basic needs of employment, food, energy, water and sanitation. There is a clear relationship between the three topics of the book: right to education has been recognized as a human right - education has a role in peace-building. Additionally, education, human rights and peace have a significant role in sustainable development. The United Nations have defined a broad range of internationally accepted rights, including civil, cultural, economic, political and social rights. However, this book demonstrates that there are still people and nations not respecting the Universal Declaration of Human Rights. Chapters from Brazil, Cameroon, Ethiopia, Kazakhstan, Israel, Peru, Russia and South-Africa cover topics like civil war, human abuses, the vulnerability of indigenous people, abortion, epilepsy, food security, lack of health equities in maternal and child health, and democracy or lack of it. We sincerely hope that this book will contribute to the joint pursuit of humanity to make the world better after we all get over the coronavirus pandemic.